Morphology and novel classification of proximal humeral fractures - Liu, Jichao; Zhang, Ziyan; Ding, Jie; Zhang, Jian; Sheng, Qian; Piao, Chengdong (Frontiers in Bioengineering and Biotechnology, 2024)
The morphology of proximal humeral fractures (PHFs) is complex, and the fixation and selection of implants need to be guided by the fracture type and classification, which requires an accurate understanding of the fracture line. This study had three purposes.(1) Define and analyze the fracture lines and morphological features of all types PHFs by three-dimensional (3D) mapping technology. (2) Determine the osteotomy position of the biomechanical model of the PHFs according to the fracture heat map. (3) Based on the analysis of the pathological morphology and distribution of a large number of consecutive cases of PHFs, propose a novel classification of PHFs.We retrospectively collected 220 cases of PHFs and generated a 3D fracture map and heat map based on computed tomography (CT) imaging. Through analysis of the fracture morphology of the 220 PHFs, a novel classification was proposed. The primary criterion for staging was the continuity between the humeral head and the greater tuberosity and lesser tuberosity, and the secondary criterion was the relationship between the humeral head segment and the humeral shaft.The fracture line was primarily found around the metaphyseal zone of region of the surgical neck, with the most extensive distribution being below the larger tuberosity and on the posterior medial side of the epiphysis. We suggest that the osteotomy gap should be immediately (approximately 5-10mm) below the lower edge of the articular surface. The most common type of fracture was type I3 (33 cases, 15.0%), followed by type IV3 fracture (23 cases, 10.4%), and type III2 fracture (22 cases, 10.0%).Interobserver and intraobserver reliability analysis for the fracture classification revealed a k value (95% confidence interval) of 0.639 (0.57-0.71) and 0.841, P<0.01, respectively.In this study, the fracture line and morphological characteristics of PHFs were clarified in detail by 3D mapping technique. In addition, a new classification method was proposed by analysis of the morphological characteristics of 220 PHFs, A two-part fracture model for PHFs is also proposed.